Research progress on the mechanism of long chain non-coding RNA AFAP1-AS1 in cancer - LI Zhiming , LONG Feng , HE Jianxin , HUANG Yong , SUN Shaokang (Zhongguo aizheng zazhi, 2021)
Cancer is one of the leading causes of death from non-infectious diseases in the whole world. Moreover, effective screening and early diagnosis and treatment of cancers have always been a major clinical difficulty. Therefore, it is urgent that novel potential biomarkers or molecular targets are identified to improve the diagnosis and treatment of cancer patients. In recent years, it has been found that long non-coding RNAs (lncRNAs) are a series of main regulatory factors in biological behaviors and diseases including tumors, and are expected to become novel biomarkers and molecular targets for tumor detection and treatment. Actin filament-associated protein 1-antisense RNA 1 (AFAP1-AS1) was initially identified as a carcinogenic lncRNA in esophageal adenocarcinoma, and later as a carcinogenic regulator of various malignant tumors. The abnormal overexpression of AFAP1-AS1 can regulate the proliferation, apoptosis, invasion and metastasis of tumor cells through different molecular mechanisms. The up- regulation of AFAP1-AS1 in tumor tissues has important clinical significance. Understanding the function and mechanism of this lncRNA in cancers can further help to explore new strategies for the prevention and treatment of malignant tumors. Therefore, this paper reviewed the effects, relevant molecular mechanisms and potential clinical significance of AFAP1-AS1 in multiple human malignant tumors, so as to provide a scientific theoretical basis for its early clinical application.